Mycobacterium tuberculosis glyceraldehyde‐3‐phosphate dehydrogenase plays a dual role—As an adhesin and as a receptor for plasmin(ogen). (16th February 2021) - Gani, Zahid; Boradia, Vishant Mahendra; Kumar, Ajay; Patidar, Anil; Talukdar, Sharmila; Choudhary, Eira; Singh, Ranvir; Agarwal, Nisheeth; Raje, Manoj; Iyengar Raje, Chaaya
Abstract: The spread of infection is directly determined by the ability of a pathogen to invade and infect host tissues. The process involves adherence due to host–pathogen interactions and traversal into deeper tissues. Mycobacterium tuberculosis (Mtb) primarily infects the lung but is unique in its ability to infect almost any other organ of the human host including immune privileged sites such as the central nervous system (CNS). The extreme invasiveness of this bacterium is not fully understood. In the current study, we report that cell surface Mtb glyceraldehyde‐3‐phosphate dehydrogenase (GAPDH) functions as a virulence factor by multiple mechanisms. Firstly, it serves as a dual receptor for both plasminogen (Plg) and plasmin (Plm). CRISPRi‐mediated silencing of this essential enzyme confirmed its role in the recruitment of Plg/Plm. Our studies further demonstrate that soluble GAPDH can re‐associate on Mtb bacilli to promote plasmin(ogen) recruitment. The direct association of plasmin(ogen) via cell surface GAPDH or by the re‐association of soluble GAPDH enhanced bacterial adherence to and traversal across lung epithelial cells. Furthermore, the association of GAPDH with host extracellular matrix (ECM) proteins coupled with its ability to recruit plasmin(ogen) may endow cells with the ability of directed proteolytic activity vital for tissue invasion.